Sex Differences in Panic-Relevant Responding to a 10% Carbon Dioxide-Enriched Air Biological Challenge - Nillni, Yael I. (2011)
The current study examined sex differences in psychological (i.e., self-reported anxiety, panic symptoms, and avoidance) and physiological (i.e., heart rate and skin conductance level) response to, and recovery from, a laboratory biological challenge. Participants were a community-recruited sample of 128 adults (63.3% women; M(age) = 23.2 years, SD = 8.9) who underwent a 4-minute 10% CO(2)-enriched air biological challenge. As predicted, women reported more severe physical panic symptoms and avoidance (i.e., less willingness to participate in another challenge) and demonstrated increased heart rate as compared to men above and beyond the variance accounted for by other theoretically-relevant variables (recent panic attack history, neuroticism, and anxiety sensitivity). Additionally, women demonstrated a faster rate of recovery with respect to heart rate compared to men. These results are in line with literature documenting sex-specific differences in panic psychopathology, and results are discussed in the context of possible mechanisms underlying sex differences in panic vulnerability.